Situational analysis of pediatric residency training program in Indonesia - Srisuparyati Soenarto; Ova Emilia (Indonesian Pediatric Society, 2006)
Background Over the last twenty years, higher education, par-ticularly pediatric residency training, has changed dramatically. Aquestion arises whether the pediatric residency training conductedin Indonesia today has been set up to meet the changing as wellas the community needs.Objective To evaluate whether the pediatric residency trainingprogram in Indonesia today has met the changing as well as thecommunity needs.Methods Twelve centers with pediatric training program in Indone-sia were involved in this study. Each institution had various numberof respondents, with a total of 42 respondents. A structured ques-tionnaire with open responses was selected to ensure the varietyand flexibility of responses.The questionnaires included statementswhich encompassed areas such as curriculum, training and educa-tional system, and alumni achievement of educational objectives.Continuous content analysis of the responses was made.Results Coverage was considered adequate by 80% of respon-dents and was suggested to be continuously updated to be in linewith existing national problems but not yet considered internationalstandard. Additional knowledge and competence proposed by therespondents are mollecular biology, genetics, generic skills, com-munication skills, and introduction to sophisticated instruments. Thelength of the existing program was appropriate. Graduate knowl-edge was sufficient and fulfilled pediatric standards. Current pro-gram was different from that of the past. The objectives are compre-hensible. The placement of trainees enabled them to follow eachdivision in a spiral fashion (at least three times during the training).Conclusion The curriculum content of the training process wascontinuously updated to be inline with existing national problems.Additional knowledge, and competence, and the present lengthof study was considered appropriate. Graduate knowledge issufficient and fulfills pediatric standards. Furthermore, the objec-tives of the current program are clearer and placement of train-ees enables them to follow each division at least three times